Impact of supplemental private health insurance on dialysis and outcomes. Issue 5 (19th May 2020) - Sriravindrarajah, Arunan; Kotwal, Sradha S.; Sen, Shaundeep; McDonald, Stephen; Jardine, Meg; Cass, Alan; Gallagher, Martin
Abstract: Background: The influence of health insurance systems on the treatment of end‐stage kidney disease (ESKD) patients ispoorly understood. Aim: We investigated how supplemental private health insurance (PHI) coverage impacted ESKD treatment modalitiesand patient outcomes. The influence of health insurance systems on the treatment of end‐stage kidney disease (ESKD) patients is poorly understood. We investigated how supplemental private health insurance (PHI) coverage impacted ESKD treatment modalities and patient outcomes. Methods: All adult patients commencing ESKD treatment in New South Wales, Australia from 2000 to 2010 were identified using the Australia and New Zealand Dialysis and Transplant Registry. Data were linked to the state hospitalisation dataset to obtain insurance status, allowing the comparisons of mortality, ESKD treatment modality and health service utilisation between privately insured and public patients. Results: The cohort of 5737 patients included 38% ( n = 2152) with PHI. At 1 year after ESKD treatment initiation, PHI patients had lower mortality (hazard ratio 0.84, 95% confidence interval (CI) 0.74–0.95, P = 0.01), were more likely to be receiving home haemodialysis (HD) (odds ratio (OR) 1.38, 95% CI 1.01–1.89, P = 0.04), to have been transplanted (OR 1.75, 95% CI 1.25–2.46, P = 0.001) and used fewer hospital days (incidence rate ratio 0.85, 95% CI 0.74–0.96, P = 0.01). After adjustment, PHI patients were more likely to initiate ESKD treatment with facility‐based HD (OR 1.22, 95% CI 1.01–1.46, P = 0.03) but were less likely to be started on peritoneal dialysis (OR 0.81, 95% CI 0.67–0.98, P = 0.03). Conclusion: Our findings suggest that supplemental PHI in Australia is associated with lower‐risk ESKD treatment attributes and improved health outcomes. A greater understanding of the treatment pathways that deliver these outcomes may inform treatment for the broader ESKD treatment population.